2018
DOI: 10.1016/j.theriogenology.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin-A and inhibin-B in cyclic and pregnant mares, and mares with granulosa-theca cell tumors: Physiological and diagnostic implications

Abstract: Studies in mares have examined serum inhibin concentrations using immuno-assays unable to distinguish dimeric inhibin-A from inhibin-B isoforms. Inhibin-A and inhibin-B immuno-assays were used to investigate concentrations in cyclic mares, young and old (6 vs 19 years old, respectively) mares following hemi-ovariectomy, mares during pregnancy and in mares with confirmed granulosa cell tumors (GCTs). Mares with inter-ovulatory intervals of 26 days had ovulatory peaks of inhibin-A averaging 80 pg/mL with a mid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
(45 reference statements)
0
12
0
1
Order By: Relevance
“…The confirmed and suspected GCTs were selected for their unusual presentation, and clinical and endocrinological progression. For instance, though most GCTs secrete increased concentrations of inhibins, 4 including inhibin B, 29 very few of the GCTs reported in this case series did. These cases are organised by ovarian size on initial clinical examination forming three groups of mares with, (a) a single, abnormally large ovary, (b) two abnormally large ovaries and (c) two ovaries of relatively normal size.…”
Section: Case Presentationmentioning
confidence: 61%
See 2 more Smart Citations
“…The confirmed and suspected GCTs were selected for their unusual presentation, and clinical and endocrinological progression. For instance, though most GCTs secrete increased concentrations of inhibins, 4 including inhibin B, 29 very few of the GCTs reported in this case series did. These cases are organised by ovarian size on initial clinical examination forming three groups of mares with, (a) a single, abnormally large ovary, (b) two abnormally large ovaries and (c) two ovaries of relatively normal size.…”
Section: Case Presentationmentioning
confidence: 61%
“…The concentration of ‘inhibins’ was increased on initial examination, but not thereafter, even though reportedly increased in normal pregnancies in mid to late gestation 43 . In contrast to ‘inhibins’, inhibin B 29 and AMH 23 are more reliable markers for GCTs, especially during pregnancy, though the current cases were not emblematic in this regard and were chosen for their unusual presentation and course. Indeed, AMH fluctuated markedly in this mare, from clearly increased (>10 ng/mL) on several occasions to within normal limits multiple times over the course of the year or more she was monitored (Figure 2), but was within normal limits at the time of surgery when the ovary was removed and the GCT was confirmed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Serum was harvested after centrifugation (1500 g for 10 min) and stored for analysis (−20°C). These samples were also included in a recently published, unrelated study evaluating inhibin-A and -B concentrations (Conley et al 2017). Unilateral ovariectomy was performed standing through a vertical flank incision of approximately 15 cm in length under sedation (detomidine, 20 μg/kg) and local anesthesia was induced by lidocaine infiltration.…”
Section: Experiments 2: Effects Of Hemi-ovariectomy On Amh Concentratimentioning
confidence: 99%
“…As one of the TGF‐β super‐family members, INHBB is commonly described as inhibitor of gonadal follicle‐stimulating hormone secretion, and INHBB has been evaluated for pregnancy‐related conditions and reproductive system tumors . Risbridger et al reported that INHB was elevated in testicular Sertoli cell tumor, adrenocortical carcinoma, and placental tumors, and lower in renal cell, hepatocellular, pancreatic, and prostate carcinomas.…”
Section: Discussionmentioning
confidence: 99%